Tratamento de sementes de feijão, soja e arroz com vinhaça de batata ( Solanum tuberosum L.) - Galli, Alberto Pahim (2011)
The vinasse of potato (Solanum tuberosum L.) has been used in an empirical way for the treatment of seeds and fertilization of different plant species in Silveira Martins, RS, Brazil. However, no information is available on its efficiency uses. The aim of the present work was to evaluate the capacity of the potato vinasse to modify the physiological quality of beans, soybeans and rice seeds. Bifatorial experiments were arranged in completely randomized and randomized blocks, each with four replicates in beans, soybeans and rice. The treatments consisted of two lots of seeds and nine concentrations of potato vinasse. The seeds were submerged in solutions of different concentrations of vinasse potato for one hour. Then, in the laboratory tests of germination, first count germination, growth and seedling dry matter biomass were carried out. The same treatments were used to evaluate the behavior of species by means of field emergence and seedling dry mass emerged. Along with the field test, we also quantified the degree of seedling development using a scale. To verify the presence of auxin, we conducted the biotest in petioles of beans. The results showed that treatment with different concentrations of vinasse potato causes physiological changes in seeds of beans, soybeans and rice observed through the expression of germination and seed vigor. Beans and soybeans have a higher number of normal seedlings in the evaluation of the first count of germination for seeds treated with concentrations of up to 20% vinasse. Concentrations above 20% do not favor germination and vigor expressions for all species. Soybean seedlings show greater length when they are originated from seeds treated with concentrations of up to 20% of potato vinasse. The concentration of 100% of vinasse potato causes a reduction in the angle formed by the petioles of beans from 180 min of immersion, which indicates the presence of auxin in this substance.